(untitled) (Asian Journal of Medical and Biological Research, 2021)
Hematological indication is an important finding for pathophysiological analysis of biological science. This study was designed with the aim to investigate the effects of residual antibiotics on hematological parameters of broiler following discriminate and indiscriminate use. The day old broiler chicks were collected and reared up to 31 days. The treatment was started from the day 16th until sacrifice. The chicks were randomly divided into three groups namely control group (Group A), discriminate antibiotic group (Group B) and indiscriminate antibiotic group (Group C) on the 14th day. The discriminate group was treated with antibiotic, colistin sulfate maintaining the withdrawal period of one week. In case of indiscriminate group the withdrawal period was not maintained and antibiotic treatment was continued till the day of sacrifice. The Hb (%) of control, discriminate and indiscriminate groups were 8.34±0.15, 6.89±0.27, and 7.14±0.23 respectively. The differences among means were statistically significant (P<0.05). The Packed Cell Volume (PCV) of control, discriminate, and indiscriminate groups were 23.51±0.76, 21.17±0.94, and 22.83±1.19 respectively. The differences among means were statistically significant. The multiple pair wise comparison of means of blood parameters revealed that there was no significant difference among discriminate and indiscriminate groups. From the above findings, this research could be considered a need based research in Bangladesh to ascertain the influential effect of antibiotic on hematological parameters in broiler. Asian J. Med. Biol. Res. 2021, 7 (2), 113-117